PRINSIP-PRINSIP OPOSISI DALAM AL-QU’RAN “Studi Analisis Pemikiran Hamka dalam Tafsir Al-Azhar” - Mun'em, Abdul (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
This writing will explain the discourse of opposition in Islamic politics in Indonesia by making Hamka and Al-Azhar’s interpretation as the object of study. The term opposition is significant because it is often misunderstood and used, both by the Western world and internally the Muslims itself. The West labels Islamic politics as anti-criticism and contrary to the spirit of democracy because it sees several Islamic countries that show more authoritarianism and dictatorship. They see that there is no justice in Islamic politics, because the opposition is second class and vulnerable to being silenced. Paradoxical phenomena are found among internal Muslims, especially in Indonesia, where it gets freedom and even guarantees in expressing their aspirations, either by sending letters, having dialogues, or even holding demonstrations on the streets. Checks and balances are the basis for the opposition movement, however, freedom of expression that exceeds the limits of reasonableness to cause anarchic and provocative actions cannot be justified because it violates the law and deviates from ethics and morality. Therefore, this study will trace Hamka’s idea of ​​ideal opposition in his interpretation by using library research and Fazlur Rahman’s double movement hermeneutic theory. With this is theory, it is found that actually the Qur’an has discussed the principles of opposition to uphold justice and eliminate the tyranny of office holders.